A Pilot Study About the Dysfunction of Adipose Tissue in Male, Sleep Apneic Patients in Relation to Psychological Symptoms - Trakada, Georgia; Nikolaidis, Pantelis T.; Economou, Nicholas-Tiberio; Sakkas, Dimitrios; Giagkou, Giorgos; Sakellariou, Stratigoula; Kyriakopoulou, Konstantina; Patsouris, Efstratios; Ferini-Strambi, Luigi; Velentza, Lemonia; Kallianos, Anastasios; Rosemann, Thomas; et al. (Frontiers in Psychiatry, 2019)
INTRODUCTION: Obstructive Sleep Apnea (OSA) and its cardiometabolic alterations are closely associated with visceral obesity. Patients with OSA frequently present with symptoms of depression and anxiety. Although these subjective symptoms of OSA are the result of complex biological dysregulation, it remains unclear if they have a direct effect on the dysfunction of adipose tissue. METHODS: In a pilot, prospective, randomized study we evaluated 10 recently diagnosed male patients with severe OSA by full polysomnography (PSG) and 4 male non apneic subjects, matched for age and Body Mass Index (BMI) with abdomen adipose tissue biopsies. Subjects with diabetes/prediabetes, cardiovascular and psychiatric disease and current smokers were excluded. All patients underwent anthropometric measurements and completed the questionnaires Epworth Sleepiness Scale (ESS), Fatigue Severity Scale (FSS) and Hospital Anxiety and Depression Scale (HADS –A and –D). Fasting venous blood samples were collected the day after PSG, between 8 and 9 AM, after an overnight fast. Fat biopsies were performed at the same time periods and adipose tissue samples of 300mg were obtained from abdominal fat. Fat cell size, extent of fibrosis, vascularity, leukocyte common antigen (LCA) inflammatory infiltration and tissue macrophages accumulation were microscopically evaluated. RESULTS: The mean age of the group was 47.4±13.8 years, with mean BMI 35.8±4.8 kg/m2 and mean Apnea / Hypopnea Index (AHI) 79.4±46.1 events per hour of sleep (severe OSA). HADS-A and HADS-D scores were 5.8±2.3 (3.0-8.0) and 4.7±2.3 (2.0-8.0), respectively. HADS-A score correlated positively with macrophages accumulation in fat biopsy (r=0.82, p=0.047), whereas ESS, FSS and HADS-D did not. Severity of fibrosis correlated largely with waist circumference (r=-0.66, p=0.038), and neck circumference (r=-0.790, p=0.006). Respiratory events correlated negatively with the extent of vascularization of adipose tissue (r=-0.614, p=0.05). CONCLUSIONS: In the preliminary results of our pilot study, we assessed that symptoms of anxiety mainly contribute to macrophages accumulation, whereas increased number of respiratory events reduces the extent of vascularization in visceral fat in OSA. Based on this observation, further larger studies are required to verify if anxious OSA patients are more vulnerable to the metabolic manifestations of the syndrome.